The influence of smartphone use on spinal posture – A laboratory study - Betsch, Marcel; Kalbhen, Kyra; Michalik, Roman; Schenker, Hanno; Gatz, Mattias; Quack, Valentin; Siebers, Hannah; Wild, Michael; Migliorini, Filippo (Gait & Posture, 2021)
Background: Smartphones have become increasingly more popular and complicated tasks can be performed with these devices. However, the increasing use is associated with shoulder and neck pain, as well as with psychological addiction. Research question: Do different smartphone tasks lead to changes in spinal posture and pelvic position? Is there a relationship between smartphone addiction and changes in posture? Methods: A cross-sectional study including 50 participants was performed. Test subjects completed the Smartphone Addiction Scale and the SF-36 health questionnaire. Subjects spinal posture and pelvic position during different smartphone tasks were measured through a surface topography system. The different tasks were: standing in an upright position, simulating a phone call, texting with one or two hands during standing or while walking on a treadmill. Paired T-tests and ANOVA tests were performed to evaluate differences. The Kendall rank test was used to investigate the association between clinical scores and changes in spinal posture. Results: All smartphone tasks lead to a significant increase in thoracic kyphosis and trunk inclination during standing and while walking. A significant increased lumbar lordosis was also found. Texting with one or two hands correlated with increased surface rotation. No associations between smartphone addiction and changes of the spinal posture were reported. Significance: This represents the first surface topography study that investigated the influence of different smartphone tasks on the spinal posture and pelvic position during standing and while walking. With the results of this study we demonstrated that smartphone use leads to significant changes of sagittal and frontal spine parameters. Further research should focus on the evaluation of possible detrimental effects of long-term smartphone use on the spinal posture and on the development of preventive measures.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Hyperkyphosis; Hyperlordosis; Smartphone; Smartphone addiction scale; Spinal posture; Surface topography